Adaptive Associations between Social Cognition and Emotion Regulation are Absent in Schizophrenia and Bipolar Disorder - Rowland, Jesseca E.; Hamilton, Meelah K.; Vella, Nicholas C.; Lino, Bianca J.; Mitchell, Philip B.; Green, Melissa J. (Frontiers in Psychology, 2013)
Schizophrenia (SZ) and bipolar disorder (BD) are associated with impairments in facial emotion perception and Theory of Mind (ToM). These social cognitive skills deficits may be related to a reduced capacity to effectively regulate one’s own emotions according to the social context. We therefore set out to examine the relationship between social cognitive abilities and the use of cognitive strategies for regulating negative emotion in SZ and BD. Participants were 56 SZ, 33 BD, and 58 healthy controls (HC) who completed the Ekman 60-faces test of facial emotion recognition; a sub-set of these participants also completed The Awareness of Social Inference Test (TASIT) and the Cognitive Emotion Regulation Questionnaire (CERQ). SZ participants demonstrated impairments in emotion perception on both the Ekman and the TASIT Emotion Evaluation tests relative to BD and HC. While both SZ and BD patients showed ToM deficits (i.e., perception of sarcasm and lie) compared to HC, SZ patients demonstrated significantly greater ToM impairment compared to BD. There were also distinct patterns of cognitive strategies used to regulate emotion in both patient groups: those with SZ were more likely to engage in catastrophizing and rumination, while BD subjects were more likely to blame themselves and were less likely to engage in positive reappraisal, relative to HC. In addition, those with SZ were more likely to blame others compared to BD. Associations between social cognition and affect regulation were revealed for HC only: TASIT performance was negatively associated with more frequent use of rumination, catastrophizing, and blaming others, such that more frequent use of maladaptive cognitive emotion regulation strategies was associated with poor social cognitive performance. These associations were not present in either patient group. However, both SZ and BD patients demonstrated poor ToM performance and aberrant use of emotion regulation strategies consistent with previous studies. SZ also showed basic emotion recognition deficits relative to BD and HC. That there were no associations between social cognition and the capacity to self-regulate negative emotion in SZ and BD (in the context of poor social cognition and maladaptive regulatory strategies) suggests that dysfunction in fronto-limbic brain networks may underpin both social cognitive deficits and the use of maladaptive cognitive strategies in these disorders, albeit by potentially different routes.